Incorporation of Selected Antimicrobial Small Molecule Compounds into Tapioca Starch and the Effects on Thickness, Moisture, and Oxygen Mass Transfer, and Mechanical Properties of the Films. (12th March 2018) - Wan, Zilu; Rajashekara, Gireesh; Fuchs, James; Carcache de Blanco, Esperanza; Pascall, Melvin A.
Abstract : The incorporation of antimicrobial small molecule compounds (JA‐144, TH‐4, and TH‐8) into tapioca starch is investigated as well as their influence on thickness, moisture uptake, gas permeation, morphology, thermal and the mechanical properties of the tapioca films. Unlike TH‐4 and TH‐8, JA‐144 increases in thickness, moisture uptake and gas permeation of the films, when compared with the control film (without antimicrobials). The melt temperature of the control is reduced from 122.63 to 119.84 °C by JA‐144, while TH‐4 and TH‐8 increases them to 126.49 °C and 130.68 °C, respectively. For JA‐144, the X‐ray diffraction show no significant crystallinity change, unlike TH‐4 and TH‐8 that show distinct crystallinity peaks. Dynamic Mechanical Analysis show that JA‐144 has little effect on the glass transition temperature and storage modulus, while TH‐4 and TH‐8 increase storage modulus and the glass transition temperature. Thus, JA‐144 increases flexibility and moisture uptake, but lowers the gas barrier. However, TH‐4 and TH‐8 augment the stiffness and gas barrier properties. Abstract : When incorporated into starch films, small molecules could be used as antimicrobial compounds and serve to increase the safety of certain foods better than macro‐molecules. Three different antimicrobial agents are tested. The small molecule (JA‐144) is found to blend best with starch films, as shown in the TOC figure, and does not negatively affect the film's mechanical, thermal, and physical properties.